Intertextual Learning Strategy Development Using POE Model on Electrolysis Cell Material to Improve Students’ Concept Mastery and Science Process Skills - Teni Dwi Yanti; Tuszie Widhiyanti; Rosyidah Syafaatur Rohmah (Jurnal Pendidikan dan Pembelajaran Kimia, 2026)
Intertextual Learning Strategy Development Using POE Model on Electrolysis Cell Material to Improve Students' Concept Mastery and Science Process Skills. This study aims to produce an intertextual learning strategy using the POE model on the electrolytic cell topic to improve students' conceptual mastery and science process skills (SPS). The method refers to the first five stages of Borg & Gall's R&D model: research and information gathering, planning, preliminary product development, preliminary product testing, and preliminary product revision. The research instruments consist of five suitability review sheets assessing the alignment among the learning objective trajectory (LOT), learning outcomes (LO), SPS indicators, concept descriptions, and learning activities. The learning strategy was designed by integrating the intertextual approach into the POE model syntax, systematically connecting macroscopic, submicroscopic, and symbolic levels of chemical representation through prediction, observation, and explanation. Based on review by six experts, inconsistencies were identified across several components, serving as the basis for comprehensive revision. The revised product is a four-cycle learning strategy covering the electrolysis of molten compounds using inert electrodes, electrolysis of solutions using inert electrodes, electrolysis of solutions using non-inert electrodes, and electrolysis applications in daily life and industry, each supplemented with quantitative aspects of Faraday's Law and designed with conceptually and pedagogically aligned SPS indicators, concept descriptions, and learning activities